Transformasi Model Kebijakan dan Perencanaan Strategis dalam Sistem Pendidikan - Khusnan Iskandar (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2022)
This article aims to explain the transformation of policy models and strategic planning in the education system which is studied theoretically based on the rules of writing scientific papers. The analysis method used in this article is a literature study and qualitative data analysis content regarding learning outcomes. The results of this study show that education policy is a product that is used as a guide for making educational decisions that are legal-neutral and moderately adjusted to the educational life environment. Meanwhile, strategic planning is the process carried out by an organization to determine a strategy or direction, as well as make decisions to allocate resources including capital and human resources. The model transformation of these two things includes institutional models, system models, investigation models, rational models, incremental models, policy analysis models, and public policy implementation approach models. The educational strategy planning models are divided into four, namely: Comprehensive planning model, Target Setting Model, Financing and cost-effectiveness model, PPBS (planning, programming, budgeting system) model